Avalia????o do potencial de reciclagem de lodo de esta????o de tratamento de esgoto na obten????o de materiais cer??micos - Hirata, Delmar (2015)
The final disposal of sewage sludge is a growing problem faced by service providers sanitation. The cycle of sludge is one of the biggest challenges of designers in the sanitation sector. Since its generation, including the treatment, storage and transportation to the alternative of disposal, the sludge must be taken into consideration in the design of a sewage treatment plant. The management of sludge is a need for sewage treatment plant that aims its effectiveness and contributing to sustainable development. Thus, to ensure that the treatment system has satisfactory results, it is necessary to make the final disposal of sewage sludge. Under suitable environmental conditions and techniques, these residues can be employed, thereby reducing the consumption of natural resources and the need for handling, storage and disposal of refuse, having as a consequence, reducing the risks generated. This work intends to evaluate aspects related to sustainability and innovation in the recycling of sewage sludge in obtaining new materials. For the formulation of the ceramic material used the experimental design {3,2}, yielding six formulations of the three components (two different types of clay and sewage sludge). Technological tests were performed in dry pieces and after sintering: linear shrinkage, water absorption, mechanical resistance to bending. The patent is an industrial property registration and at the same time contains information that can be used for technological development. To retrieve patent information processing and recycling of sewage sludge was held in Patentinspiration search database, available from AULIVE. Were used as key words to search the terms "Sewage Sludge", "Recycle", "Treatment", "Ceramic Materials" among others. 1.377 patent applications were recovered using the terms "treatment" and "Sewage Sludge". The sintered ceramic materials developed with the addition of sewage sludge, the present physical property values which make it possible to use this residue as an alternative raw material for the production of ceramic products.